2005
DOI: 10.1029/2004ja010698
|View full text |Cite
|
Sign up to set email alerts
|

An ice‐cream cone model for coronal mass ejections

Abstract: [1] In this study, we use an ice-cream cone model to analyze the geometrical and kinematical properties of the coronal mass ejections (CMEs). Assuming that in the early phase CMEs propagate with near-constant speed and angular width, some useful properties of CMEs, namely the radial speed (v), the angular width (a), and the location at the heliosphere, can be obtained considering the geometrical shapes of a CME as an ice-cream cone. This model is improved by (1) using an ice-cream cone to show the near real co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 23 publications
1
106
0
6
Order By: Relevance
“…This measurement shows that the projection effect was lowest for the SOHO view compared to other views from the STEREO satellites. We confirmed the above argument again by applying the ice cream cone model of CME (Xue et al 2005) to the LASCO CME data and found that the source longitude of the CME is E89. These results are consistent with the study by Gopalswamy et al (2009), who reported the expected source locations (E102, E81, and E58) of the CME deduced from the different views of SA, SOHO, and SB, respectively.…”
Section: -D Cme Kinematicssupporting
confidence: 68%
“…This measurement shows that the projection effect was lowest for the SOHO view compared to other views from the STEREO satellites. We confirmed the above argument again by applying the ice cream cone model of CME (Xue et al 2005) to the LASCO CME data and found that the source longitude of the CME is E89. These results are consistent with the study by Gopalswamy et al (2009), who reported the expected source locations (E102, E81, and E58) of the CME deduced from the different views of SA, SOHO, and SB, respectively.…”
Section: -D Cme Kinematicssupporting
confidence: 68%
“…By combining the ice cream cone model (Xue et al 2005) and CME deflection model , we find that besides the obvious factor of the source region location, the span angle and the deflection are also important in determining the probability of a CME impacting an object such as the Earth. The large span angles of some CMEs (e.g., the second, third, and possible fourth) account for the fact that they are observed by the Wind spacecraft (i.e., they hit the Earth), even though their source region locations are not close to the solar central meridian.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, many researchers suggest that the geometrical properties of most CMEs could be inferred indirectly by a cone model (Howard et al 1982;Fisher & Munro 1984;Leblanc et al 2001;Zhao et al 2002;Michalek et al 2003;Xie et al 2004). Recently, an ice cream cone model was further developed by Xue et al (2005), whose work showed consistency between the fitted and observed speeds of CMEs.…”
Section: Ice Cream Cone Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where φ/2 represents the cone half-angle expressed in radians, i.e., φ is the CME-cone angular width (for details of the cone model see Zhao et al 2002;Michałek et al 2003;Xie et al 2004;Schwenn et al 2005;Xue et al 2005). Below we assume that the width φ and the CME mass m do not change significantly beyond r = 20 r .…”
Section: The Modelmentioning
confidence: 99%